2014
DOI: 10.22436/jmcs.011.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Fairness Aware Downlink Scheduling Algorithm For Lte Networks

Abstract: This paper proposes a new scheduling algorithm in downlink Long Term Evolution networks whichis adoptable with fast variations in channel conditions.It allocates resources in a fair manner among users so that it increases cell edge users' performance. Besides, it makes a good trade-off between throughput and fairness. The proposed method is simulated and compared with three scheduling algorithms available for Long Term Evolution. The results showgood degree of fairness at the cost of small decrease in amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…(4) when determining the priority of each user on each RB, on each CC and at each time. Besides the extended versions of the M-LWDF, other studies that investigated the packet scheduling algorithms in the literature include [6][7][8][9][10][11][12][13][14]. Based on our study, it was observed that the majority of these conventional multi-user packet scheduling algorithms offer to meet the desired QoS of either for RT packets or NRT packets.…”
Section: Introductionmentioning
confidence: 74%
“…(4) when determining the priority of each user on each RB, on each CC and at each time. Besides the extended versions of the M-LWDF, other studies that investigated the packet scheduling algorithms in the literature include [6][7][8][9][10][11][12][13][14]. Based on our study, it was observed that the majority of these conventional multi-user packet scheduling algorithms offer to meet the desired QoS of either for RT packets or NRT packets.…”
Section: Introductionmentioning
confidence: 74%
“…In the air interface, Bahreyni and Sattari-naeini in 2014 [4] proposed a new scheduling algorithm for LTE networks that supports rapid channel variations and aims to increase system capacity while maintaining fairness when the number of active users is greater than the number of existing RBs. This algorithm improved the performance of cell edge users based on the preferences of users with less bandwidth.…”
Section: Existing Methodsmentioning
confidence: 99%
“…The proposed algorithm tries to balance between fairness and spectral efficiency, as it enhances fairness in terms of throughput among the UEs while retaining the spectral efficiency. Moreover, another fairness aware scheme is proposed in [24] to adopt fast variations in channel conditions. The proposed technique fairly allocates resources between UEs to enhance the performance of the cell edge users [24].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, another fairness aware scheme is proposed in [24] to adopt fast variations in channel conditions. The proposed technique fairly allocates resources between UEs to enhance the performance of the cell edge users [24]. Nevertheless, these algorithms do not account for the QoS requirements for different UEs, which leads to performance degradation [25].…”
Section: Related Workmentioning
confidence: 99%